PENGARUH KETERLIBATAN KERJA PEGAWAI TERHADAP KINERJA KARYAWAN SAAT MASA PANDEMI COVID-19 - Rahma Tia; Muhammad Fathin Mahdi; Neuneung Ratna Hayati (Universitas Bina Taruna Gorontalo, 2022)
This study aims to determine whether or not there is an influence of work engagement on employee performance during the Covid-19 pandemic. Research using quantitative methods involved 122 employees of Kimia Farma Pharmacy Business Unit Jayapura City, Papua. The results of the study indicate that employees perceive work involvement and their performance at a moderate level on average. In addition, the hypothesis test conducted shows that work involvement has a positive influence on the performance of Kimia FarmaApotek Business Unit employees in Jayapura City, Papua. Kimia Farma Pharmacy Business Unit Jayapura City, Papua. Having the opportunity to improve the employee experience during the Covid-19 pandemic phase by focusing on employee health and safety towards a more nuanced approach to creating a work environment that encourages passion, dedication, and devotion to serving customers.